Social Media Guidelines for Anatomists. Issue 4 (6th May 2020) - Hennessy, Catherine M.; Royer, Danielle F.; Meyer, Amanda J.; Smith, Claire F.
Abstract : Social Media has changed the way that individuals interact with each other ‐ it has brought considerable benefits, yet also some challenges. Social media in anatomy has enabled anatomists all over the world to engage, interact and form new collaborations that otherwise would not have been possible. In a relatively small discipline where individuals may be working as the only anatomist in an institution, having such a virtual community can be important. Social media is also being used as a means for anatomists to communicate with the current generation of students as well as members of the public. Posting appropriate content is one of the challenges raised by social media use in anatomy. Human cadaveric material is frequently shared on social media and there is divided opinion among anatomists on whether or not such content is appropriate. This article explores the uses and challenges of social media use in the field of anatomy and outlines guidelines on how social media can be used by anatomists globally, while maintaining professional and ethical standards. Creating global guidelines has shown to be difficult due to the differences in international law for the use of human tissue and also the irregularities in acquiring informed consent for capturing and sharing cadaveric images. These nuances may explain why cadaveric images are frequently shared on social media. This article proposes that as standard practice, anatomists obtain informed consent from donors before sharing images of cadaveric material on social media and ensure posts include a statement stating the same.